Ta'thir madrasah Han Sue bi-al-Sin fi fahm ahkam al-Islam: Dirasah usiliyah naqdiyah / Musa Ibn Sulayman Al-Sinni - Musa Ibn Sulayman, Al-Sinni (2012)
Since more than 400 years, two Muslim scholars of China whom are Wang Dai Yu (1570-1660) and Liu Zhi (1660-1730) have adopted the teachings of Confucius in order to make comparison to Islamic law. It is done in order to harmonize Chinese thought with Islamic thought. This kind of doctrine plays a role in realizing the practice of fekah law voluntarily and spontaneously. The basics of these thoughts are gradually strengthened through a series of works translated from Arabic into Chinese “Han”. These efforts continued until the time of Ma Qi Xi (1857-1914), founder of the Taoist notion of Western. He formed a perfect “Han Xue” stream - from some of the features - with cross-cultural transformation. After 400 years had passed, there were among his followers whom called to ‘Chinese-size’ the readings of the Quran through sing-song form similar to Chinese Opera. The effort was up to the stage requiring the reading of the Quran through Chinese-sizatio in prayer. This phenomenon makes the researcher interested in order to do a study of the positive and negative effects of the phenomenon. This research focuses on the following aspects which are the explanation about the arrival of Islam in China, the streams found in Chinese-Muslim societies, the definition of Han Xue stream, its history, well-known figures and its relation to Confucianism. In addition to these, the study also focuses on the concept of moderation in Islam, the similarities and differences in moderation in Confucianism and Buddha-Confucianism in terms of understanding the tenants of Islam and its implementation. It also compares the three aforementioned perspectives with Usul Fiqh.